2009
DOI: 10.1007/s11274-009-0152-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal remediation of Amarula distillery wastewater

Abstract: Amarula Cream is an alcoholic beverage derived from the distillation of fermented marula fruit and to date there is no scientific data as to the characteristics of the distillery wastewater generated from its production. The wastewater was found to have a chemical oxygen demand (COD) of 27 g/l, a pH of 3.8, a high concentration of phenolic compounds (866 mg/l) and a high suspended solids content (10.5 g/l), all of which could adversely affect biological treatment. Full-strength wastewater was treated using sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…On the other hand, Shayegan et al [23] mentioned that decolorization can reach a maximum value and then decrease slightly, while the pH increase due to repolymerization of melanoidin. Strong [24] in the treatment of Amarula distillery wastewater (27 g/L of COD and 866 mg/L of phenolic compounds) with Trametes pubescens reported that the concentration of phenolic compounds would lead to a great increase in color when the pH increased from 3.8 to neutral. The color change observed may be attributable to the conversion of the phenol to the quinone version in a hydroxyl-rich solution (by abstraction of the hydrogen cation from the OH group of the phenol).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Shayegan et al [23] mentioned that decolorization can reach a maximum value and then decrease slightly, while the pH increase due to repolymerization of melanoidin. Strong [24] in the treatment of Amarula distillery wastewater (27 g/L of COD and 866 mg/L of phenolic compounds) with Trametes pubescens reported that the concentration of phenolic compounds would lead to a great increase in color when the pH increased from 3.8 to neutral. The color change observed may be attributable to the conversion of the phenol to the quinone version in a hydroxyl-rich solution (by abstraction of the hydrogen cation from the OH group of the phenol).…”
Section: Resultsmentioning
confidence: 99%
“…The color change observed may be attributable to the conversion of the phenol to the quinone version in a hydroxyl-rich solution (by abstraction of the hydrogen cation from the OH group of the phenol). Also, it is known that the first step for degradation by fungi is adsorption [24, 25], and pH of the solution affects this step because the fungal cell wall is composed of polysaccharides (i.e., chitin and chitosan), proteins, lipids, and melanin with several functional groups (amino, carboxyl, thiol, and phosphate groups) capable of binding various organic molecules. The ionic forms of these organic compounds in solution and the surface electrical charge of the biomass depend on the pH solution.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, VS are released to surface waters causing significant environmental problems (Beltr an et al, 1999). The amount of VS generated is 8e15 times greater than the ethanol production (Strong, 2009). In addition, the VS are produced in large quantities in a short season, making its treatment a harder challenge (Vlyssides et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Food waste, olive oil mill wastewaters, industrial fats and whey and starch hydrolyses were other wastes for microbial lipid production by oleaginous fungi (Amaral et al 2012;Fakas et al 2008;Zhu et al 2003). Strong (2009) used four fungi to reduce COD in distillery wastewater. This study determined that using fungi could reduce oil waste pollutions and production of valuable products.…”
Section: Bod and Cod Assaymentioning
confidence: 99%